Analisis Environmental, Social, Governance Disclosure dan Financial Performance Terhadap Volatilitas Harga Saham - Nur Isnaini Faizatul Ummah; Subadriyah Subadriyah (Forum Kerjasama Pendidikan Tinggi, 2026)
This study focuses on analyzing how Environmental, Social, and Governance (ESG) disclosures and financial performance influence stock price volatility in the food and beverage industry listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024. Using secondary data from annual reports, sustainability reports, and historical stock prices, this study employed a quantitative methodology. Purposive sampling was used to select 35 companies as the research sample. Using SPSS version 26, the analysis technique used multiple linear regression. The findings indicate that environmental and social disclosures have a significant negative effect on stock price volatility. Conversely, governance disclosures have a significant positive effect. Meanwhile, volatility is not significantly affected by financial performance as determined by Return on Assets (ROA), indicating that in the post-pandemic food and beverage sector, investors tend to prioritize sustainability factors and non-financial risk mitigation, as reflected in ESG disclosure, over short-term profitability. The R2 value of 13.8% indicates that external factors outside the research model influence most of the variations in stock price volatility. The contribution of this research lies in providing empirical evidence on the role of ESG disclosure in explaining stock price volatility in the food and beverage sector post-pandemic, as well as providing influence for company management and investors in formulating their variance strategies and making risk-based investment decisions.